Nutritional and Metabolic Status Control and Nutritional Support in Patients with Pancreatic Sepsis (Review) - A. V. Zhukov; A. I. Gritsan; K. Y. Belyaev; I. P. Belyaeva (Общая реаниматология)
Acute pancreatitis (AP) is associated with pancreonecrosis in 30% of patients, who may fall at 80% high risk of death when infected pancreatic necrosis progresses to sepsis. Given the catabolic nature of the disease and the signiﬁcant inﬂuence of nutritional status on its course and outcome, these patients require an adequate nutritional support (NS) based on an adequate assessment and control of nutritional and metabolic status.The aim of the study: to identify trends in developing new tools for assessment of nutritional and metabolic status, and provision of NS in patients with pancreatic sepsis (PS).Materials and methods. Keyword search in the PubMed, Scopus and E-library databases for the period from 2018 to 2023 yielded 95 publications, of which 16 meta-analyses and 6 systematic reviews met the requirements.Results. all existing to date scales for assessment of nutritional deﬁciency in patients with PS have low prognostic value. Of them, mNUTRIC scale seems to be the most appropriate assessment tool. Recommended by EPSEN guidelines tools to assess the risk of nutritional deﬁciency it is not suitable for ICU patients. Indirect calorimetry should be preferred vs routine calculation formulas in assessing patient’s energy needs in case of PS. It was also found that «standard» anthropometric values, such as BMI, are not always informative and prognostically signiﬁcant in patients with severe AP in the ICU. Analgesia, infusion therapy, as well as detection and correction of intraperitoneal hypertension are not only integral components of intensive care for PS but are indispensable for supplying adequate NS in PS patients. It was found that early enteral nutrition is the preferred method of NS, although questions concerning choice of tube insertion site, as well as all parameters of tube feeding remain unanswered. The optimal composition of enteral nutrition for patients with PS has not been established, which is indirectly conﬁrmed by the variety of enteral mixtures available on the market. The refeeding syndrome that occurs at initiation of NS was characterized as a life-threatening condition.Conclusion. NS, based on adequate assessment of disorders and control of the nutritional and metabolic status is an integral component of intensive care in PS patients. It can reduce the probability and number of potential complications, time of stay in the ICU, cost of treatment, and improve patient’s prognosis.